The Combination of Soursop and Turmeric Leaf Extracts Improves Lipid Profiles in Metabolic Syndrome Model Mice - Bagas Widiyanto; Natasya Intan; Nurul Kurnia Thoyibah; Yumna Sudjudi; Anggita Sabila Faza (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Soursop and turmeric leaves have been studied to contain secondary metabolites such as flavonoids, saponins, tannins, sitosterol, and curcumin, which have the potential to prevent metabolic syndrome. The aim of this study was to determine the ability of a combination of soursop leaf extract and turmeric to improve lipid profile levels in metabolic syndrome rat models of total cholesterol (KT,) LDL, Tligserida (TG), HDL, and VLDL. This experimental research design used the post-test only control group design method. A total of 36 rats were randomly divided into 6 groups, the normal group (N); metabolic syndrome(SM); SM+atorvastatin 0.18 mg/200 gBB (SMA); SM+combination of soursop leaf extract and turmeric of 150:50 mg/kgBB(K1); SM+combination of soursop leaf extract and turmeric 100:100 mg/kgBB(K2); SM+combination of soursop leaf extract and turmeric 50:150 mg/kgBB(K3). The mean levels of KT, TG, LDL and VLDL in the K2 groups were significantly lower than the SM group (p-value<0,05). Compared to HDL levels in the K2, which were significantly higher than the SM group (p-value<0,05). So, the combination of soursop leaf extract and turmeric improved the lipid profile in the metabolic syndrome rat model with the best dose of 100:100 mg/kgBB.